Building inherently impactful research programs: the role of organizational context. Issue 3 (3rd July 2021) - Barbara, Julien; Haley, Nicole; McMahon, Hannah; Turnbull, Timothea
Abstract: Much impact research focuses on how individual scholars can influence policy outcomes, leading to recommendations about how individual researchers can be more entrepreneurial and engage with policy cycles in innovative ways. This approach is problematic in that it reinforces assumptions about researchers as "heroic" individuals, obscuring consideration of how organizational contexts support or hinder the prospects for research impact. As a result, the importance of organizational context is frequently absent from universities' impact strategies. This article seeks to address this gap by presenting a case study on the experiences of the Department of Pacific Affairs (DPA) at the Australian National University (ANU) in creating a context that supports research impact. DPA's research approach has long included a strong policy focus, aided in part by long-term financial support from the Australian government to build a globally preeminent center of excellence for policy-relevant research on the Pacific. Concentrating on DPA's organizational context as an impact mechanism, the article considers lessons learned that can inform the development of research contexts that serve as an inherently impactful approach to research.